Urban growth and waste management optimization towards 'zero waste city' - Zaman, Atiq; Lehmann, S. (2011)
Today, many developed cities such as Stockholm, and Adelaide are aiming to transform their current waste management practice into a more efficient and sustainable way, called zero waste practice. Increasingly people move from rural to urban environments due to the economic activities and quality of life provided to inhabitants, causing cities to expand. Over-crowded cities are compromising the quality of urban life due to their rapid growth and ever-increasing generation of waste. The concept of the " zero waste city" includes a 100% recycling rate and recovery of all resources from waste materials. However, transforming current over-consuming cities to zero waste cities is challenging. Therefore, this study aims to understand the key drivers of waste management and the challenges, threats, and opportunities in transforming traditional waste streams and optimizing practices toward zero waste practices. Part of this study is an in-depth case analysis of waste management systems in two cities, Adelaide and Stockholm. Cities from high consuming countries, such as Australia and Sweden, have been analyzed based on five waste management contexts: social, economic, political, technological, and environmental. In addition, key drivers are identified. Both Adelaide and Stockholm have the vision to become " zero waste cities". The study concludes that strategies based on tools, systems, and technologies can assist cities in their transformation into " zero waste cities" ; however, they must also be affordable, practicable, and effective within their local regulatory framework.